Optimization and Purification of Terpenyl Flavor Esters Catalyzed by Black Cumin (Nigella sativa) Seedling Lipase in Organic Media - Haq, Naveed Ul; Liaquat, Muhammad; Alharby, Hesham F.; Alzahrani, Yahya M.; Alghamdi, Sameera A.; Alharbi, Basmah M.; Alabdallah, Nadiyah M.; Saud, Shah; Ahmed, Mukhtar; Sayyed, R. Z.; Fahad, Shah (Frontiers in Sustainable Food Systems, 2022)
Geranyl butyrate and citronellyl butyrate esters are industrially important fruity flavors that are being used in food and as a fragrance in cosmetics. Previously terpenyl fruity flavors have been successfully synthesized in organic solvents using crude seedlings enzymes. The purpose of the current study was to standardize reaction parameters for the optimal synthesis of geranyl butyrate using the best chosen black cumin seedling lipase in an organic medium through direct esterification reactions. Geranyl butyrate and citronellyl butyrate esters were identified, quantified through gas chromatography, confirmed through GC-MS, and partiallypurified through the distillation process. Effect of organic solvents (acetonitrile, n-hexane, pentane, heptane, and toluene), alcohol and acid concentrations (0.125–0.3 M), temperature (20–50°C), incubation time (1–72 h), and enzyme concentrations (0.05–0.3 g) were studied on the synthesis of geranyl butyrate using black cumin seedling lipase. The highest conversion yields of ester (96%) were obtained when 0.25 M of geraniol and butyric acid were reacted at 37°C for 48 h in the presence of 0.25 g of crude seedling lipase enzyme in n-hexane. It was concluded that the germinated black cumin seedling lipase proved to be the best among the selected biocatalysts for the synthesis of geranyl butyrate in n-hexane.